IMPLEMENTATION OF ASSOCIATION RULE METHOD USING APRIORI ALGORITHM FOR BOOK SHELF ARRANGEMENT RECOMMENDATION AT THE LIBRARY AND ARCHIVES OFFICE OF BENGKULU PROVINCE - Naufallah, Muflih Rasyid; Abdullah, Dedy; Darmi, Yulia; Rifqo, Muhammad Husni (Institut Bakti Nusantara, 2025)
In a library, the ability to process data is very necessary, from the data that has been processed can be obtained information related to borrowing patterns from visitors. Dinas Perpustakaan dan Kearsipan Provinsi Bengkulu is a public library that has a collection of 34,559 which is divided into various types of collections. Due to the large number of collections, visitors have difficulty in finding the desired book. Therefore, this research will apply the association rule method using the a priori algorithm to find borrowing patterns from visitors so that it can become a benchmark in compiling collections at the Bengkulu Province Library and Archives Office. The apriori algorithm is an algorithm that can find a frequency in data. By using this algorithm, it can find borrowing patterns from visitors.